Pencemaran Air dan Penentuan Titik Self-Purification Sungai di Kabupaten Banjar - Zubaidah, Tien; Hamzani, Sulaiman; Arifin (Department of Environmental engineering, Faculty of Science and Technology, Islamic State University Sunan Ampel Surabaya, 2021)
The self-purification capacity is an important indicator for a healthy river. Organic and inorganic pollutants from various pollutant sources, both point sources, and non-point sources, in most rivers in Banjar Regency, cause a decrease in river water quality. This study aims to identify the distribution of river water quality pollution in Banjar Regency as the upstream of the Martapura River and determine the point of self-purification. A sampling of river water using the purposive sampling technique, taking into account the criteria for pollutant sources and the distance of pollution. The results of the concentration values were analyzed using a trend analysis technique, which connected the value of the concentration of pollutant elements with the distance of pollution to identify the distribution of pollution, and to determine the distance of purification. The results showed that the self-purification ability (pH and DO) decreased in concentration at all observation points.